1979
DOI: 10.1007/bf00973677
|View full text |Cite
|
Sign up to set email alerts
|

Extensive sclerosis of the base of the skull due to primary nasal tuberculosis

Abstract: An 8 year old black male is presented as a primary nasal tuberculous granuloma whose roentgenograms of the skull revealed extensive sclerosis of the periorbital region involving the frontal, sphenoid, and petrous bones. The tuberculous meningitis and the osseous sclerosis at the base of the skull were cured with anti-tuberculous therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In this review surgical excision resulted in a recurrence rate of greater than 50%. Reported cases since 1951 have been treated with anti‐TB, medications, and no recurrences have occurred, except for one case, noted by Nemir et al 13 in which the patient was noncompliant. Current recommendations for EPTB treatment are identical to those for pulmonary TB: isoniazid, rifampin, and pyrazin‐amide for 2 months, followed by isonizid and rifampin alone for 4 months 2 .…”
Section: Discussion and Literature Reviewmentioning
confidence: 97%
“…In this review surgical excision resulted in a recurrence rate of greater than 50%. Reported cases since 1951 have been treated with anti‐TB, medications, and no recurrences have occurred, except for one case, noted by Nemir et al 13 in which the patient was noncompliant. Current recommendations for EPTB treatment are identical to those for pulmonary TB: isoniazid, rifampin, and pyrazin‐amide for 2 months, followed by isonizid and rifampin alone for 4 months 2 .…”
Section: Discussion and Literature Reviewmentioning
confidence: 97%
“…Primary tuberculosis of the nasal mucosa is rare. Since it was first described by Clarke in 1876 (Clarke, 1876), a further 34 cases have been reported in the literature (Clarke, 1876;Havens, 1931;Messervy, 1971;Nemir et al, 1979;Page and Jash, 1974;Sharan, 1981;Waldman etal., 1981). Tuberculosis is often included in the differential diagnosis of nasal granulomatous disease, but it is not generally considered as a poss-ible cause of a unilateral nasal fossa mass.…”
Section: Introductionmentioning
confidence: 99%
“…In 1852, Willigk [3] reported 1 patient of nasal tuberculosis among 476 patients of tuberculosis. Nemir et al [4] reported involvement of base of skull in one case. Gleitsmann1, in 1907, reported that a search of the literature revealed only 20 cases of maxillary sinus.…”
Section: Discussionmentioning
confidence: 96%